ENRAIZAMENTO DE ESTACAS DE KIWIZEIRO COM FITORREGULADORES NAS QUATRO ESTAÇÕES DO ANO - Paes, Elisangela da Graça Boeno (Scientia Agraria, 2003)
Propagation of the kiwifruit (Actinidia deliciosa A. Chevallier (C. F. Lang et A. R. Ferguson)) usually is done through grafting of crown over rootstocks. Aiming to decrease time for formation of rootstocks followed by grafting, the present appears as an alternative for the species propagation utilizing direct cutting from crown as a technique for faster speed and efficiency. Different concentrations of synthetic auxins, indolebutyric acid (lBA) and naphtaleneacetic acid (NAA), in solution and powder, were applied in the kiwifruit stem cuttings of Bruno, Abbott and Monty cultivars, originated of commercial plants from Boutins farm, located at Porto Amazonas, PR. They were collected during the four-year seasons (autumnl2001, winter/2001, spring/2oo1 and summer/2002). The stem cuttings were prepared with approximately 12 cm length, average diameter of 0,65 cm being their bases immersed for 10 seconds in the solutions and in powder combinations as follows: T1: distilled water; T2: 2500 mg.L-1 IBA (solution); T3: 5000 mg.L-1 IBA (solution); T4: 2500 mg.L-1 NAA (solution); T5: 5000 mg.L-1 NAA (solution); T6: inert powder; T7; 2500 mg.Kg-1 IBA (powder); T8: 5000 mg.Kg-1 IBA (powder); T9; 2500 mg.Kg-1 NAA (powder); T1O: 5000 mg.Kg-1 NAA (powder). Data were analyzed within each station separately, according to a complete randomized design with factorial arrangement of 1O treatments over 3 cultivars, with 4 replications per combination, being the experimental units composed of 1O cuttings. Cuttings were planted in plastic containers using vermiculite as growing media and kept in greenhouse with intermittent mist. After 70 days the following variables were observed: rooted stem cutting percentage; number of roots per stem cutting; length of the three bigger roots per stem cutting; callus stem cutting percentage; alive stem cutting and dead stem cutting percentage. Through this work it was possible to conclude that there is heterogeneity of the rooting potential among the studied cultivars; summer and spring showed high death rate; the largest rooting average was obtained with 5000 mg. Kg-1 NAA in powder, for Bruno (70,0%) and Monty (40,0%) cultivars in winter, and 5000 mg L-1 NAA in solution for Abbott cultivar (37,0%) in summer.